2022-RA-1667-ESGO Topical imiquimod cream for recurrent vulvar Paget disease. (20th October 2022) - Kardhashi, Anila; Popescu, Ondina; de Benedictis, Lucrezia; Cazzolla, Ambrogio; Silvestris, Erica; Loizzi, Vera; Arezzo, Francesca; Mongelli, Michele; Cormio, Gennaro
Abstract : Introduction/Background: Extramammary Paget disease (EMPD) is a rare entity, accounting for only 6% of all Paget disease (PD). It is a neoplasm that frequently presents in areas where apocrine glands are abundant, such as the anogenital region and, less frequently, the axillae, with the vulvar area being the most frequently involved location. Surgery, with total excision, remains the treatment of choice, although other therapeutic approaches such as radiotherapy, photodynamic therapy, CO2 ablative laser therapy, interferon alpha, topical 5-fluorouracil (5-FU) and topical 5% imiquimod have been used with variable success. Regardless of the adopted therapy, the disease seems to follow a chronic course with high relapsing rates, ranging from 15 to 72%. Imiquimod, an immunomodulatory agent, is the most commonly used off-label topical treatment of EMPD, with varying response rates ranging from 50% to 100%. However, the indications to the use of imiquimod remain unclear. We studied the Imiquimod cream to avoid the serious anatomical, psychological and functional sequelae of surgery in case of recurring EMPD. Methodology: In this study we describe three cases of recurrent EMPD (after 4 years of follow-up), which had positive margins after undergoing primary surgery for PDV. A skin biopsy confirmed the clinical suspect of a recurrent disease, in a non-invasive form. Considering the lesions extent we decided to use imiquimod cream three applications per week for 12 weeks. Results: As shown by the pictures below, in two out of three patients we achieved the complete clinical response and the third patient had an improvement of the symptoms, althought the lesion persisted. Some of the side effects of imiquimod were erythema, pruritus, pain. All patients correctly completed the treatment. Conclusion: Topical 5% imiquimod cream can be an effective and safe alternative treatment for noninvasive recurrent Paget disease, compared to the surgical excision.